Evaluation of curing units used in private dental offices in Tehran in 2005 - Mirzaei M; Moradimajd N (Tehran University of Medical Sciences, 2007)
Background and Aim: Light cured composites and other restorative materials are quite common in dentistry today. Successful restorations are dependent on efficiency of curing light unit, eg. the intensity of emitted light and its wave length. The aim of this study was to evaluate the efficiency units of curing, in private dental offices in Tehran. Materials and Methods: In this descriptive cross sectional study, light curing devices in 240 private dental offices were evaluated randomly. Light intensity was measured by radiometer, debris on the fan and cracks and scratches on the filter were directly observed and the age of the device, frequency of changing the bulb and satisfaction of the dentist with regard to the light curing unit were recorded in a questionnaire. Data were analyzed using Spearman and t test, with p<0.05 as the level of significance.Results: The results showed that 53.8% of the units had intensities more than 300 mW/cm2. The intensity of 30.4% of curing light units were between 20 and 300 mW/cm2 and 15.8% had intensities lower than "n200 mW/cm2. There was a negative relation between light intensity and the age of the unit, frequency of bulb changing or scratches on the filter and debris on the fan.Conclusion: The results of this study showed that the light intensities of about 46% of light curing units used in private dental practices and clinics were inadequate. Since factors like aging of the curing light unit, frequent bulb changing, increasing the amount of debris on the fan and scratches on the filter reduce the light intensity, regular quality control of these devices is essential.